Engineered Functional Surfaces by Laser Microprocessing for Biomedical Applications. (December 2018) - Hu, Guoqing; Guan, Kai; Lu, Libin; Zhang, Jiaru; Lu, Nie; Guan, Yingchun
Abstract: Metallic biomaterials are increasingly being used in various medical applications due to their high strength, fracture resistance, good electrical conductivity, and biocompatibility. However, their practical applications have been largely limited due to poor surface performance. Laser microprocessing is an advanced method of enhancing the surface-related properties of biomaterials. This work demonstrates the capability of laser microprocessing for biomedical metallic materials including magnesium and titanium alloys, with potential applications in cell adhesion and liquid biopsy. We investigate laser-material interaction, microstructural evolution, and surface performance, and analyze cell behavior and the surface-enhanced Raman scattering (SERS) effect. Furthermore, we explore a theoretical study on the laser microprocessing of metallic alloys that shows interesting results with potential applications. The results show that cells exhibit good adhesion behavior at the surface of the laser-treated surface, with a preferential direction based on the textured structure. A significant SERS enhancement of 6 × 10 3 can be obtained at the laser-textured surface during Raman measurement.